A multi-targeting drug design strategy for identifying potent anti-SARS-CoV-2 inhibitors - Ren Peng-xuan; Shang Wei-juan; Yin Wan-chao; Ge Huan; Wang Lin; Zhang Xiang-lei; Li Bing-qian; Li Hong-lin; Xu Ye-chun; Xu Eric H.; Jiang Hua-liang; Zhu Li-li; et al. (Acta Pharmacologica Sinica, 2022)
The COVID-19, caused by SARS-CoV-2, is threatening public health, and there is no effective treatment. In this study, we have implemented a multi-targeted anti-viral drug design strategy to discover highly potent SARS-CoV-2 inhibitors, which simultaneously act on the host ribosome, viral RNA as well as RNA-dependent RNA polymerases, and nucleocapsid protein of the virus, to impair viral translation, frameshifting, replication, and assembly. Driven by this strategy, three alkaloids, including lycorine, emetine, and cephaeline, were discovered to inhibit SARS-CoV-2 with EC50 values of low nanomolar levels potently. The findings in this work demonstrate the feasibility of this multi-targeting drug design strategy and provide a rationale for designing more potent anti-virus drugs.